Why Study Millennialism Today?: Plenary Lecture Delivered to the British Association for the Study of Religions, 11 September 2023 - Wessinger, Catherine (Journal of the British Association for the Study of Religions, 2025)
Various types of millennial expressions give meaning to believers' lives. Many millennial movements do not cause harm, but there are occasions on which millennialists either resort to violence or become caught up in violence within interactive contexts. Revolutionary millennial movements have the potential for the greatest amount of violence. Since this lecture was delivered on the morning (in the United States) of 11 September 2023, the twenty-second anniversary of the 9/11 attacks by al-Q?'ida operatives, in remembrance of the nearly 3,000 victims of the attacks, al-Q?'ida is examined as a transnational nativist millennial movement. A similarity in an outlook of victimhood and dispossession from God-given religious and cultural supremacy can be discerned among radical Islamists and former President Donald Trump's mostly white, mostly Christian, MAGA followers. There are important reasons relating to politics, terrorism, and conflicts, as well as to what David Feltmate (2016) terms "social possibilities" in new religious movements to study millennialism today. Distinctive millennial patterns - benign and involved in violence - are delineated, in addition to discussing leaders who utilize their socially constructed charisma for benevolent purposes, and the narcissism of leaders of millennial movements who motivate followers to commit violence.